The Shared Duality of Self-training and Co-design of an EAS for a Resilient Transformativeness - Brunetti, Immacolata (Formazione & insegnamento, 2022)
The theory of self-determination (SDT) is a rapidly expanding topic, which helps us to consider personal abilities regarding self-regulation and self-determination of one’s learning, as well as vulnerability to defensive and control. Within the SDT, these human abilities are studied using different methods of psychology. In this research we focus, in particular, on the capacity for autonomy in the self-training decision. On the basis of self-training, this contribution aims to reflect on the meaning of didactic co-planning shared between teachers in smart working (Alessandrini, 2016), on the action that the teacher performs during the redesign of the contents to be taught (Perla-Riva, 2016). Working with new methodologies requires a new way of rethinking oneself as a teaching professional (Rivoltella-Rossi, 2012). The cosharing of choices regarding the content, the resources available, and their skills starting from their training, highlights the figure of the teacher as a designer who redesigns his teaching project every day, moving from motivations to self-training (Knowles , 1975; Quaglino, 2014; Bochicchio, 2014).